2021
DOI: 10.1101/2021.04.22.21255924
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resting-state functional MRI signal fluctuations are correlated with brain amyloid-β deposition

Abstract: Mounting evidence suggests that amyloid-β (Aβ) and vascular etiologies are intertwined in the pathogenesis of Alzheimer′s disease. Spontaneous fluctuations of the brain blood-oxygen-level-dependent (BOLD) signal, as measured by resting-state functional MRI (rs-fMRI), have been shown to be associated with neuronal activities as well as cerebrovascular hemodynamics. Nevertheless, it is unclear if rs-fMRI BOLD fluctuations are associated with brain Aβ deposition in individuals with an elevated risk of Alzheimer's… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…Similarly, more recent evidence reported differences in FC dynamic states dwell time between AD patients and control groups and further observed lower dynamic FC variability in Alzheimer patients 43 and in relationship with transient changes in cognition typical of early stages of neurodegenerative disease. 44 In line with our results, recent work has also suggested that early amyloid deposition in the brain reduces variations of rs-fMRI BOLD signal 45 and FC 41 over time in cognitively unimpaired individuals.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, more recent evidence reported differences in FC dynamic states dwell time between AD patients and control groups and further observed lower dynamic FC variability in Alzheimer patients 43 and in relationship with transient changes in cognition typical of early stages of neurodegenerative disease. 44 In line with our results, recent work has also suggested that early amyloid deposition in the brain reduces variations of rs-fMRI BOLD signal 45 and FC 41 over time in cognitively unimpaired individuals.…”
Section: Discussionsupporting
confidence: 92%
“…Previous research had proved that DMN connectivity dysfunction was associated with amyloid burden in the cognitively normal elderly (Sheline et al, 2010;Mormino et al, 2011;Wang et al, 2013b;Elman et al, 2016;Palmqvist et al, 2017). Moreover, in the Scheel et al study, a robust negative correlation between ALFF signals and the amyloid load was predominantly in the DMN and visual network, in the amnesic MCI group (Scheel et al, 2021). The negative correlation shown in the ACC for both SCD and T2DM groups may illustrate the vulnerability of the ACC to amyloid pathology.…”
Section: Partial Correlation In T Dm and Scd Groups: Cortex Id Roi-basedmentioning
confidence: 76%
“…An alternative to GSR is to regress out the average signals derived only from the white matter (WM) and cerebrospinal fluid (CSF), where neuronal contributions are thought to be negligible ( Bartoň et al, 2019 ). The WM-CSF regression approach found considerable application ( Satterthwaite et al, 2013 ; Parkes et al, 2018 ; He et al, 2020 ; Scheel et al, n.d. ). However, there is evidence that WM also contains information about brain function ( Ding et al, 2013 ; Mazerolle et al, 2013 ; Peer et al, 2017 ; Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%